2014
DOI: 10.13168/agg.2014.0006
|View full text |Cite
|
Sign up to set email alerts
|

Damane evolution law based on acoustic emission and weibull distribution of granite under uniaxial stress

Abstract: The research on rock damage mechanisms during loading has a significant reference value for the deformation damage issues in the rock engineering industry. In this paper, Electrohydraulic Servo Material Test System MTS815 and PCI-2 based AE System were utilized for uniaxial compression tests of granite specimens and acoustic emission monitoring tests during the compression respectively. According to the test data, there is a well defined correspondence between the curves of acoustic emission count rate with ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Rock mechanics studies have been extensively conducted in China and abroad, which cover a broad range, from uniaxial to triaxial compression, simple to multiple conditions, and single to complex paths [1][2][3][4][5][6]. In triaxial tests, the initial stress level mainly includes the initial confining pressure and the initial axial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Rock mechanics studies have been extensively conducted in China and abroad, which cover a broad range, from uniaxial to triaxial compression, simple to multiple conditions, and single to complex paths [1][2][3][4][5][6]. In triaxial tests, the initial stress level mainly includes the initial confining pressure and the initial axial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The constitutive model of rock material is the foundation for design and assessment in rock engineering. Many attempts have been made to propose constitutive models to simulate for rock damage behaviour (Wang et al, 2007;Zhou and Zhu, 2010;Ji et al, 2014;Nazarova et al, 2015). Shojaei et al (2014) developed a continuum damage mechanics based constitutive model to describe elastic, plastic and damage behavior of porous rocks.…”
mentioning
confidence: 99%
“…Ji et al [31] also proposed a constitutive model for two kinds of rocks, but the tting results were not good. Ji et al concluded that the constitutive relationship can only partially represent the loading characteristics of rock.…”
Section: Experimental Validation Of Modelsmentioning
confidence: 99%
“…paper by Ji et al[31] Theoretical curve 1 in paper by Ji et al[31] (R 2 = 0.5548) Theoretical curve 2 in paper by Ji et al[31] (R 2 = 0.3046) Theoretical curve in this paper (R 2 = 0.7913) Stress (MPa) paper by Ji et al[31] Theoretical curve 1 in paper by Ji et al[31] (R 2 = 0.2819) Theoretical curve 2 in paper by Ji et al [31] (R 2 = 0.5427) Theoretical curve in this paper (R 2 = 0.6956) Stress (MPa) paper by Ji et al [31] Theoretical curve 1 in paper by Ji et al [31] (R 2 = 0.4394) Theoretical curve 2 in paper by Ji et al [31] (R 2 = 0.3695) Theoretical curve in this paper (R 2 = 0.7679Curves of the theoretical tting from Ji et al [31]. (a) Sample no.…”
mentioning
confidence: 98%